Students’ Interest in Start Up Business: A Systematic Literature Review - Verawati, Rika; Yacoob, Mohd. Rafi (Journal of Advanced Research in Business and Management Studies, 2024)
To minimize the increasing unemployment rate in various countries, one solution that can be taken is to encourage students to start start-up businesses through increasing entrepreneurial interest. The formulation in this study is what countries have studied entrepreneurial interest in higher education and how to implement entrepreneurship education in various universities. This study aims to determine what countries have studied entrepreneurial interest in higher education and describe how entrepreneurship education is implemented in multiple universities. The steps of this review include searching, screening, evaluating, and synthesizing—30 articles published in popular Scopus journals. The study shows that 12 countries have examined the importance of entrepreneurial interest and the role of entrepreneurship education in developing a culture of innovation, risk-taking, and business creation among university students. The potential impact on economic development is significant, as entrepreneurial students create jobs for themselves and generate innovations that can drive overall economic growth.